The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10151-016-1506-7
|View full text |Cite
|
Sign up to set email alerts
|

Damage control strategy for the treatment of perforated diverticulitis with generalized peritonitis

Abstract: Damage control strategy in patients with generalized peritonitis due to perforated diverticulitis leads to a significantly reduced stoma rate after the initial hospital stay without an increased risk of postoperative morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 21 publications
1
43
0
3
Order By: Relevance
“…With its mortality rate said to range from 11% to 33.3%, colon perforation requires intensive postoperative care. As a tertiary emergency medical institution, our hospital is equipped with an intensive care unit and can manage such treatments as artificial respiration, postoperative OAM, polymyxin B‐direct hemoperfusion, continuous hemodiafiltration, and others.…”
Section: Discussionmentioning
confidence: 99%
“…With its mortality rate said to range from 11% to 33.3%, colon perforation requires intensive postoperative care. As a tertiary emergency medical institution, our hospital is equipped with an intensive care unit and can manage such treatments as artificial respiration, postoperative OAM, polymyxin B‐direct hemoperfusion, continuous hemodiafiltration, and others.…”
Section: Discussionmentioning
confidence: 99%
“…Some patient series have investigated laparoscopic closure of a perforation combined with laparoscopic lavage but there is little evidence to support this practice [120]. There are some studies suggesting damage control with a second look within a couple of days [116,121]. Neither are established techniques.…”
Section: Should a High-fibre Diet Be Recommended Following An Episodementioning
confidence: 99%
“…Although there was no difference in postoperative mortality, patients who underwent DCS followed by a second-look laparotomy with closure 24 hours to 48 hours later had a reduced stoma rate (83% vs 47%, p=0.038). 44 The exact parameters when to consider DCS for the emergency general surgery patient are not as well outlined as in the trauma setting. 45 46 A retrospective study of general surgery patients who underwent DCS found that indications should include severe sepsis/septic shock, elevated lactate >3, acidosis (pH<7.25), age >70 years, male gender, and multiple pre-existing comorbidities.…”
Section: Abdominal Compartment Syndromementioning
confidence: 99%